Research on privacy preserving mechanism of attribute-based encryption cloud storage - Tao FENG; Xiao-yu YIN (网络与信息安全学报)
The typical cloud storage architecture was presented as research objects and the privacy preserving mechanism of attribute-based encryption cloud storage including following aspects-data owner,cloud servers,au-thorized agency,data user and revocation of user was researched.By analyzing and comparing,it was discovered that the privacy preserving problems of cloud storage could be divided into privacy issues of users' identity,sensitive attribute information disclosure and leakage of privacy content in the system.Aiming at the above problems,the current privacy preserving mechanism of attribute-based encryption cloud storage was studied and shortages of the present schemes,possible solutions and the study trend in the future were discussed.